Blunting neuroinflammation with resolvin D1 prevents early pathology in a rat model of Parkinson’s disease - Krashia, Paraskevi; Cordella, Alberto; Nobili, Annalisa; La Barbera, Livia; Federici, Mauro; Leuti, Alessandro; Campanelli, Federica; Natale, Giuseppina; Marino, Gioia; Calabrese, Valeria; Vedele, Francescangelo; Ghiglieri, Veronica; et al. (Nature communications, 2019)
Neuroinflammation is one of the hallmarks of Parkinson’s disease (PD) and may contribute to midbrain dopamine (DA) neuron degeneration. Recent studies link chronic inflammation with failure to resolve early inflammation, a process operated by specialized pro-resolving mediators, including resolvins. However, the effects of stimulating the resolution of inflammation in PD – to modulate disease progression – still remain unexplored. Here we show that rats overexpressing human α-synuclein (Syn) display altered DA neuron properties, reduced striatal DA outflow and motor deficits prior to nigral degeneration. These early alterations are coupled with microglia activation and perturbations of inflammatory and pro-resolving mediators, namely IFN-γ and resolvin D1 (RvD1). Chronic and early RvD1 administration in Syn rats prevents central and peripheral inflammation, as well as neuronal dysfunction and motor deficits. We also show that endogenous RvD1 is decreased in human patients with early-PD. Our results suggest there is an imbalance between neuroinflammatory and pro-resolving processes in PD. Resolvins are endogenous lipids with pro-resolving activity. Here the authors find that rats overexpressing human α-synuclein show defects in dopamine signalling before dopamine cell loss, and that this is associated with low Resolvin D1 levels and neuroinflammation.